Investigating The Integration Of Critical Pedagogy In Teaching English As A Foreign Language: Perspectives From Senior High School Teachers In Palu - Mulky Satria Kamal; Darmawan Darmawan; Mashuri Mashuri; Maf’ulah Maf’ulah (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study investigates the integration of Critical Pedagogy in teaching English as a Foreign Language (EFL) based on the perspectives of senior high school teachers in Palu, Indonesia, within the framework of the Merdeka Belajar curriculum. Using a qualitative research design, this study explores how teachers understand and apply key principles of Critical Pedagogy, such as dialogue, problem-posing, reflection and action (praxis), and the development of students’ critical awareness of social issues. Data were collected through classroom observations and in-depth interviews with three purposively selected EFL teachers. The findings reveal that the teachers have attempted to implement student-centered learning through classroom discussions, problem-solving tasks, and project-based learning connected to local contexts, including disaster awareness and community issues. However, several challenges were identified, including curriculum constraints, limited teaching resources, insufficient professional development opportunities, and students’ limited readiness for critical engagement. This study concludes that the effective integration of Critical Pedagogy in EFL classrooms in Eastern Indonesia requires context-sensitive teacher training, greater curricular flexibility, and stronger policy support to promote critical and socially responsive English language teaching.